Expression of a vitelline membrane protein, BmVMP23, is repressed by bmo‐miR‐1a‐3p in silkworm, Bombyx mori. Issue 7 (26th February 2013) - Chen, Anli; Xia, Dingguo; Qiu, Zhiyong; Gao, Peng; Tang, Shunming; Shen, Xingjia; Zhu, Feng; Zhao, Qiaoling
Abstract : Previous studies have shown that the 3′ UTR of BmVMP 23 was destroyed by an inserted fragment, and the BmVMP 23 expression was downregulated in the lethal egg of "Ming" ( l ‐ e m ). In this study, we found a miRNA (bmo‐miR‐1a‐3p) that matches the 3′ UTR sequence of BmVMP 23 perfectly. The relationship between bmo‐miR‐1a‐3p and the BmVMP 23 expression was examined by the co‐transfection in vitro. The luciferase assay result showed that luc expression was strongly repressed. This result inferred that bmo‐miR‐1a‐3p may downregulate BmVMP 23 expression via complementary interaction with the target sites at the 3′ UTR. Abstract : ► This paper is the first report on the bmo‐miR‐1a‐3p expression in the ovary of the silkworm. ► Bmo‐miR‐1a‐3p expression level is related to BmVMP23 expression level. ► Bmo‐miR‐1a‐3p repressed luc expression that ligated the 3′ UTR sequence of BmVMP23 in vitro.